E-Module Development of Linear Programs Based on Students' Conceptual Understanding - Lestari, Fransiska Dwi; Syahbana, Ali; Retta, Allen Marga (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
The purpose of this study is to create an E-Module based on conceptual understanding of linear programming that is valid, practical, and understands the potential effects of E-Modules. The Research and Development (RD) method was used in this study. This study employs the ADDIE model development procedure, which consists of five stages: analysis, design, development, implementation, and evaluation. The E-Module is declared